2011
DOI: 10.1159/000328781
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab in the Treatment of Advanced, Non-Squamous Non-Small Cell Lung Cancer: An Evidence-Based Approach

Abstract: Background: To assess the efficacy and safety of bevacizumab-containing regimens in the treatment of advanced, chemotherapy-naive, non-squamous non-small cell lung cancer (NSCLC) on the basis of the two registrative trials [ECOG E4599 trial and BO17704 (AVAiL) trial]. Methods: A pooled analysis of the two trials was performed using a random effect model, and the results were summarized as number-needed-to-treat (NNT) and number-needed-to-harm (NNH). A 2-step analysis was performed. The primary analysis include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Adenocarinomas had lower BAP1 expression than squamous tumors (38% vs. 58.3%, respectively). Although non-squamous histology is a criterion for bevacizumab [17,18,19] as well as pemetrexed treatment [17,20,21], many patients with adenocarinoma are not sensitive to these drugs [22,23,24]. us, new targets for e ective drugs are always needed.…”
Section: Discussionmentioning
confidence: 99%
“…Adenocarinomas had lower BAP1 expression than squamous tumors (38% vs. 58.3%, respectively). Although non-squamous histology is a criterion for bevacizumab [17,18,19] as well as pemetrexed treatment [17,20,21], many patients with adenocarinoma are not sensitive to these drugs [22,23,24]. us, new targets for e ective drugs are always needed.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that intrapleural injection of platinum chemotherapy drugs combined with bevacizumab reduced the incidence of chest pain (1.72 times) and mitigated the dyspnea of patients with MPE (3.07 times), compared with platinum chemotherapy drugs alone, which indicated that intrapleural injection of bevacizumab participation improved the QOL of patients with MPE. Previous study shows that adding bevacizumab to standard chemotherapy in the treatment of advanced non-squamous NSCLC seems to favor a modest improvement in the main outcomes [ 9 , 33 ] and bevacizumab significantly prolongs OS and progression-free-survival (PFS) when added to first-line platinum-based chemotherapy in patients with NSCLC [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, many clinical studies have indicated several limitations to the application in those therapies [3,4]. Although they kill tumor cells, chemotherapy damage normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular targeted therapeutics for NSCLC have been developed such as bevacizumab [1] and gefitinib [2]. However, there have been severe side effects in those therapies [3,4]. Therefore, novel treatment methods with no side effects are required to improve quality of life for patients.…”
Section: Introductionmentioning
confidence: 99%